A systematic investigation to establish a structure-property correlation in 0.65PMN–0.35PT ceramics - Garg, T.; Mukesh, M.; Goyal, Lickmichand M.; Mir, Kifayat H. (Journal of materials science. Materials in electronics, 2024)
In this work, we present a systematic and detailed study on synthesis and characterization of near morphotropic phase boundary (MPB) composition, 0.65PMN–0.35PT {0.65Pb(Mg 1/3 Nb 2/3 )O 3 –0.35PbTiO 3 } ceramics prepared by columbite method. Phase purity and crystal structure of the prepared ceramics were studied using X-ray diffraction. Single-phase PMN-PT ceramics were subject to structural, dielectric, ferroelectric, piezoelectric, and electromechanical characterizations. Phase analysis using Rietveld refinement of XRD pattern of these ceramics revealed presence of rhombohedral and tetragonal phases of PMN–PT confirming composition to near MPB. A highly dense microstructure was observed from field emission gun-scanning electron microscopy (FEG–SEM) with a relatively smaller grain size at a comparatively lower sintering temperature. Dielectric measurements indicated a broad diffused phase transition. Ferroelectric studies revealed a square loop hysteresis at room temperature with relatively large coercivity. A strong piezoelectric behavior was observed by strain versus electric filed measurement at 1 Hz. A comparison of the observed values of various parameters with existing literature on these ceramics has been made to establish exclusivity of our results.